Foliar habit, tolerance to defoliation and their link to carbon and nitrogen storage. (1st July 2014) - Piper, Frida I.; Fajardo, Alex; Heil, Martin
Summary An innovative hypothesis to explain the higher carbon (C) and nitrogen (N) storage in woody tissues of winter deciduous species as compared to evergreen species is that these storages reflect an adaptation to tolerate herbivory. Support for this hypothesis has been little when manipulative defoliations were partial and/or applied in a single season. Given that repeated defoliations throughout a single season are common in temperate forests and tend to be more severe in deciduous than in evergreen species, we tested this hypothesis considering complete and recurrent defoliation in two sympatric Nothofagus species with contrasting foliar habit. In the field, we applied three defoliation intensities for 3 years in naturally coexisting juvenile trees of Nothofagus betuloides (evergreen) and Nothofagus pumilio (deciduous). Defoliation intensities included complete defoliation (100%) twice during the growing season, partial defoliation (50%) twice during the whole experiment and no defoliation. We evaluated survival, regrowth and C‐ and N‐storage in the leaves, stems and roots of each tree. Complete defoliation caused 100% mortality in N. betuloides after the first year and no mortality in N. pumilio after 3 years; it induced higher C reductions in N. pumilio roots, supported by greater C‐storage. Partial defoliation caused no interspecific differences in survival, though it produced a stronger decrease in C‐storage in N. betuloides than in N. pumilio. N concentrations in woody tissues were significantly higher in N. pumilio than in N. betuloides, and only in the former did they decrease with the defoliation intensity. Synthesis. We found a potential functional link between leaf habit, defoliation tolerance and C‐ and N‐storage. The deciduous species tolerated complete and recurrent defoliations better than the evergreen species, which was associated with higher C‐ and N‐storage in stems and roots of the former. This link was not detected under partial defoliation. We suggest that the higher C‐ and N‐storage in the woody tissues of deciduous species as compared to evergreen species is an adaptation to tolerate complete and recurrent defoliations under which temperate winter deciduous species may have evolved.